Coordinated Development of the Competitiveness System of Urban Exhibition Industry: A Case of Guangzhou, Shenzhen, Dongguan, and Zhongshan Cities - Chen Yilu; Li Lixun; Fu Tianlan (Redai dili, 2022)
The exhibition industry is characterized by high efficiency and high economic relevance, making it one of the most active components of China's modern service industry. Previous studies have revealed that the competitiveness of the urban exhibition industry results from multiple factors, such as the scale of the exhibition industry, the level of economic development, related facilities, and the service industry in cities. However, a few cities in China have ignored their functional positioning and resource constraints in recent years, thus blindly constructing super large-scale venues that far exceed demand. This abnormal phenomenon shows that the level of coordinated development among elements significantly impacts the urban exhibition industry. Therefore, this study focuses on the coordination of the key supporting elements for the exhibition industry. First, we constructed a comprehensive index system to evaluate the competitiveness of the urban exhibition industry, which consisted of exhibition industry vitality, economic strength, and reception capacity subsystems. Second, we used the coupling coordination model of physics to calculate the coupling coordination degree among these three subsystems in Guangzhou, Shenzhen, Dongguan, and Zhongshan. The exhibition industry of these four cities develops most prosperously among the mainland cities in the Guangdong-Hong Kong-Macao Greater Bay area. By comparing the results between these four cities from 2013 to 2019, we aimed to explore the constraints of the coordinated development of the urban exhibition industry's competitiveness system and the interactive mechanism between subsystems. These results show a significant hierarchical difference among the four cities in the level of coordinated development of the exhibition industry's competitiveness. Guangzhou and Shenzhen have already reached the premium coupling coordination stage, where subsystems resonate benignantly, and the degree of coupling coordination is relatively high. In contrast, the degree of coupling coordination is still low for Dongguan and Zhongshan, indicating that the exhibition industry is developing extensively in these two cities. The coordination mechanism is a process wherein the exhibition industry vitality, economic strength, and reception capacity subsystems are synchronized and closely integrated toward the same direction. In this situation, the subsystems develop to a certain level, and the mutual forces between them form a loop that circulates both clockwise and counterclockwise, with the exhibition vitality acting as the core, the reception capacity as the foundation, and the economic strength as the development element. Different cities have diverse main constraints on the coordinated development of the exhibition industry's competitiveness. For first-tier cities, their comprehensive service capability is more crucial than their economic strength, which is related to the market size of the city's exhibition industry. For non-first-tier cities, their economic strength often determines whether the urban exhibition industry that serves the local area can have an impetus for sustained growth because the overall service industry is underdeveloped.